Apparent Parameters of Enzymatic Plate-Gap Electrode - Kaunietis, I.; Šimkus, R.; Laurinavičius, V.; Ivanauskas, F. (Nonlinear Analysis: Modelling and Control, 2005)
It was suggested that reaction-diffusion conditions in pores of bulk enzymatic electrode resemble particular conditions in thin enzyme filled gap between parallel conducting plates. The plate-gap model of porous enzymatic electrode is based on the diffusion equations containing a nonlinear term related to the Michaelis-Menten kinetics of the enzymatic reaction inside the gap. Steady state current was calculated for the wide range of given values of substrate diffusion coefficient, depth of the gap and substrate concentrations. Simple approximate relationships between “apparent” parameters of amperometric biosensor (maximal currents and apparent Michaelis constants) and given values of diffusion characterising parameters were derived. Association of these dependences with previously reported relationships led to derive approximate formulae that bind apparent parameters with the complete set of given parameters of the plate-gap enzymatic electrode. The limit case of slow diffusion into deep gap was also characterised. In this specific case, the highest numerical values of the apparent parameters were obtained. However, this gain is achievable at the expense of biosensor response time.
Keywords: reaction-diffusion; modelling; amperometric biosensors; porous electrode